A mixed methods evaluation of the acceptability of therapy using LEGO® bricks (LEGO® based therapy) in mainstream primary and secondary education. Issue 7 (9th April 2022) - Barr, Amy; Coates, Elizabeth; Kingsley, Ellen; de la Cuesta, Gina Gomez; Biggs, Katie; Le Couteur, Ann; Wright, Barry
Abstract: Many autistic children and young people need extra support with social skills. Social skills programmes, such as LEGO® based therapy (LBT), are commonly used to help with these difficulties. The aim of this study was to examine the acceptability of LBT using qualitative interviews and questionnaires with facilitators and parents/guardians on behalf of autistic children and young people. Acceptability was measured in line with constructs of the Theoretical Framework of Acceptability. Questionnaires were analyzed descriptively and between group comparisons were undertaken using the Mann–Whitney U Test. Telephone interviews were undertaken with a sub‐sample of facilitators. All interviews were recorded, transcribed verbatim, and framework analysis was performed by two researchers supported by NVivo. The questionnaire response rate was 80% for facilitators and 77% for parents/guardians. Overall acceptability, measured on a 1–5 (minimum–maximum) scale, was high for both facilitators and parents/guardians with a median (range) of 5 (4–5) and 4 (3–5), respectively. Facilitators rated the acceptability of the programme significantly higher overall than parents ( p < 0.001). Facilitators reported that participants and wider school staff viewed the programme positively. They observed improvements in communication and social skills during the sessions. Potential barriers to programme delivery, such as resources and staff schedules, were identified but facilitators reported that these challenges did not outweigh the benefits. There is increasing emphasis on the role of schools in seeking to improve social outcomes for autistic children therefore this high degree of acceptability makes this an attractive school‐based programme for schools, autistic children and their families. Lay Summary: Social skills programmes, such as LEGO® based therapy (LBT), are often used to help autistic children and young people with their social skills. The acceptability of LBT with school staff and parents/guardians on behalf of children and young people was explored using interviews and questionnaires. Our results show that LBT is viewed as a highly acceptable programme that can help autistic children and young people improve their communication and social skills.